Sex hormones and immune system: Menopausal hormone therapy in the context of COVID-19 pandemic - Averyanova, Marina; Vishnyakova, Polina; Yureneva, Svetlana; Yakushevskaya, Oksana; Fatkhudinov, Timur; Elchaninov, Andrey; Sukhikh, Gennady (Frontiers in Immunology, 2022)
The fatal outcomes of COVID-19 are related to the high reactivity of the innate wing of immunity. Estrogens could exert anti-inflammatory effects during SARS-CoV-2 infection at different stages: from increasing the antiviral resistance of individual cells to counteracting the pro-inflammatory cytokine production. A complex relationship between sex hormones and immune system implies that menopausal hormone therapy (MHT) has pleiotropic effects on immunity in peri- and postmenopausal patients. The definite immunological benefits of perimenopausal MHT confirm the important role of estrogens in regulation of immune functionalities. In this review, we attempt to explore how sex hormones and MHT affect immunological parameters of the organism at different level (in vitro, in vivo) and what mechanisms are involved in their protective response to the new coronavirus infection. The correlation of sex steroid levels with severity and lethality of the disease indicates the potential of using hormone therapy to modulate the immune response and increase the resilience to adverse outcomes. The overall success of MHT is based on decades of experience in clinical trials. According to the current standards, MHT should not be discontinued in COVID-19 with the exception of critical cases.